Mathematical Literacy and Its Teaching: Exploring the Understanding and Readiness of Indonesian Preservice Mathematics Teachers - Sumbaji Putranto; Ibrahim (Indonesian Journal of Mathematics Education, 2026)
Mathematical literacy is a key 21st-century competency that enables students to solve mathematical problems across various real-world contexts. This study aims to explore preservice mathematics teachers’ understanding of mathematical literacy, their knowledge of teaching mathematical literacy, and their readiness to implement it in classroom practice. It also investigates the influence of gender, theoretical coursework, and teaching practice experience on these three aspects. The quantitative phase used a questionnaire as the data-collection instrument and involved 114 preservice teachers, while the qualitative phase included interviews with 10 participants. Quantitative data were analyzed descriptively and continued with independent samples t-tests, whereas qualitative data were analyzed through reduction, presentation, and verification to deepen the interpretation of findings. Preservice mathematics teachers in Indonesia showed a good understanding of mathematical literacy (M = 3.21), a very good understanding of mathematical literacy instruction (M = 3.37), and good readiness to teach mathematical literacy (M = 2.94). Independent samples t-test results revealed that gender had no significant effect (p > .05), theoretical coursework significantly influenced understanding of mathematical literacy (p = .016), and teaching practice experience significantly affected understanding of mathematical literacy (p = .020), understanding of mathematical literacy instruction (p = .037), and readiness to teach mathematical literacy (p = .043). These findings highlight the importance of integrating theory and practice in teacher education, through microteaching, lesson study, and field experiences, to strengthen preservice teachers’ professional competence in fostering mathematical literacy in the classroom.